Intravascular large B-cell lymphoma as a recurrence of primary central nervous system lymphoma after chemotherapy: A case report. (2021) - Edahiro, Yoko; Takaku, Tomoiku; Suzuki, Mario; Fukuda, Yasutaka; Harada, Sakiko; Kinoshita, Shintaro; Inano, Tadaaki; Shirane, Shuichi; Hamano, Yasuharu; Kondo, Akihide; Komatsu, Norio
Abstract: We report about a 48-year-old woman diagnosed with primary central nervous system lymphoma (PCNSL). After chemotherapy and autologous stem cell transplantation, she presented with a continuous high-grade fever. Positron emission tomography-computed tomography revealed prominent hepatosplenomegaly and high diffuse uptake of 18F-fluorodeoxyglucose in the liver, spleen, and lungs. Intravascular large B-cell lymphoma (IVLBCL) was diagnosed using random skin biopsy. There were no symptoms of IVLBCL at the time of diagnosis of PCNSL. The histopathological features of PCNSL and IVLBCL were nearly similar. These findings suggest that IVLBCL was the recurrence of PCNSL rather than a separate entity.